2008
DOI: 10.3858/emm.2008.40.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Cross talk between P2 purinergic receptors modulates extracellular ATP-mediated interleukin-10 production in rat microglial cells

Abstract: Previously we demonstrated that ATP released from LPS-activated microglia induced IL-10 expression in a process involving P2 receptors, in an autocrine fashion. Therefore, in the present study we sought to determine which subtype of P2 receptor was responsible for the modulation of IL-10 expression in ATP-stimulated microglia. We found that the patterns of IL-10 production were dose-dependent (1, 10, 100, 1,000 µM) and bell-shaped. The concentrations of ATP, ATP-γS, ADP, and ADP-β S that showed maximal IL-10 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 34 publications
(32 reference statements)
1
26
1
Order By: Relevance
“…We then determined if P2Y 4 receptors were expressed in microglia. Previous studies had identified that microglia express mRNAs encoding P2Y 4 receptors (19,21,22). We confirmed the expression of the P2Y 4 receptor at the protein level by Western blotting (Fig.…”
Section: Nucleotides Evoke Pinocytosis In Microgliasupporting
confidence: 82%
“…We then determined if P2Y 4 receptors were expressed in microglia. Previous studies had identified that microglia express mRNAs encoding P2Y 4 receptors (19,21,22). We confirmed the expression of the P2Y 4 receptor at the protein level by Western blotting (Fig.…”
Section: Nucleotides Evoke Pinocytosis In Microgliasupporting
confidence: 82%
“…The P2Y receptors, for example, were shown to inhibit release of TNF-␣, IL-1␤, IL-6, and IL-12 in LPSactivated cultured rat and mice microglia (82,669). In contrast, the activation of P2Y 1 /P2Y 11 receptors increased IL-10 expression and release in LPS-activated rat microglia (820,821). The activation of P2Y receptors in cultured microglia also resulted in rapid accumulation of immediate early genes c-fos, junB, c-jun, and TIS11 (725).…”
Section: P2y Receptorsmentioning
confidence: 99%
“…This suggests that P2Rs also have a function which counteracts the effect of proinflammatory mediators [167,168].…”
Section: Interleukin-6-type Of Cytokinesmentioning
confidence: 99%